Endoscopic prediction of tumor invasion depth in early gastric neoplasia: a prospective study in Peru - Palacios Salas, Fernando (2017)
Introduction: Endoscopic resection is the first option treatment of early gastric cancer with invasion to mucosa or superficial submucosa, because the risk of nodal metastasis is negligible. Then the prediction of tumor invasion is cardinal. Objectives: Determine the accuracy of endoscopic prediction for tumor invasion depth in early gastric neoplasia and define endoscopic characteristics associated with massive submucosal invasion. Materials and methods: Prospective sudy of diagnostic test validation. We included patients with early gastric neoplasias that were endoscopically or surgically resected from January 2012 to May 2016. Every lesion was looked for the presence of these features: margin elevation, central elevation, irregular surface, enlarged folds, size > 30mm and rigidity. The invasion prediction was categorized in: M-Sm1 when none feature was present, Sm2 when 2 or more features were present, and indeterminated when only one feature was present. We compared endoscopic prediction to pathological staging and determined diagnostic accuracy. Results: The global accuracy for endoscopic prediction was 98.2%. Sensitivity, specificity, positive and negative predictive values for M-Sm1 prediction were 97.6, 100, 100 y 92.8%, and for Sm2 prediction were 100, 97.6, 92.8 y 97.6%, respectively. Rigidity, irregular Surface, margin elevation and enlarged folds were associated with Sm2 invasion. Conclusions: Endoscopic prediction of tumor invasion depth in early gastric neoplasia is very accurate. The main endoscopic feature associated with Sm2 invasion is rigidity.